Pengaruh Komunikasi, Work Life Balance dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Dinas Pendidikan Provinsi Jawa Barat - Putri, Nathania Amelia; Siddiq, Andhika Mochamad; Muttaqin, Ridlwan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research analyzes the influence of communication, work-life balance, and work motivation on job satisfaction of West Java Provincial Education Service employees, with an initial survey showing a low level of satisfaction. Using a descriptive and verification quantitative approach, data was collected through questionnaires from 100 respondents selected using purposive sampling. Data were analyzed using multiple linear regression. The research results show that communication, work-life balance, and work motivation have a significant effect on job satisfaction. Specifically, communication (p = 0.001), work-life balance (p = 0.000), and work motivation (p = 0.000) have a positive effect. The F test shows the calculated F value is 244,161 (p = 0.000), indicating the simultaneous influence of the three variables on job satisfaction. These findings conclude that effective communication, good work-life balance, and high work motivation contribute to increasing employee job satisfaction.